An exploration of the progress of open crime data: how do ongoing limitations with the Police.uk website restrict a comprehensive understanding of recorded crime? - Quinn, Anthony (Policing and society, 2019)
Open-source crime data provided by the Police.uk website was introduced in 2008. This provision challenged what had been termed a ‘top down’ political culture and was introduced to help increase government transparency and accountability. We examine these concepts here and outline some of the significant developments over the last decade related to the information contained within the Police.uk resource. Our focus then moves towards limitations of the data set provided, some of which are as pervasive today as they were when this online data source was first introduced. We explore whether these drawbacks are irresolvable and consider the practical implications they will have when this open data set is utilised by members of the public and researchers. Ultimately, we give an assessment of the efficacy of this source of information for the user within the context of the government rhetoric which accompanied it.